2000
DOI: 10.1038/sj.onc.1203756
|View full text |Cite
|
Sign up to set email alerts
|

Conformational phenotype of p53 is linked to nuclear translocation

Abstract: P53 is inactivated in tumors by mechanisms other than mutations in the p53 gene itself. To gain insight into the mechanisms by which this inactivation occurs, we chemically mutagenized A1-5 cells expressing high levels of temperature sensitive p53 val135 (tsp53) and selected for clones that were capable of growth at the permissive temperature for p53 activation. We expanded 22 clones (ALTR cells for A1-5 Low Temperature Resistant) that could grow at the permissive temperature. Most exhibited cytoplasmic seques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
(36 reference statements)
1
20
0
1
Order By: Relevance
“…Previously, we showed that ALTR cells with cytoplasmically sequestered tsp53 at 321C also exhibited a predominantly mutant conformation of tsp53 and only in cells with nuclear-localized p53 was the tsp53 present in a wildtype conformation, suggesting that there is a correlation between the localization of p53 protein and its conformation (Gaitonde et al, 2000). This correlation suggests that there is a link between protein conformation and nuclear localization.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previously, we showed that ALTR cells with cytoplasmically sequestered tsp53 at 321C also exhibited a predominantly mutant conformation of tsp53 and only in cells with nuclear-localized p53 was the tsp53 present in a wildtype conformation, suggesting that there is a correlation between the localization of p53 protein and its conformation (Gaitonde et al, 2000). This correlation suggests that there is a link between protein conformation and nuclear localization.…”
Section: Discussionmentioning
confidence: 79%
“…The immunoprecipitation and indirect immunofluorescence were performed as described previously (Gaitonde et al, 2000).…”
Section: Rt-pcr and Sequencing Of P53 Val135mentioning
confidence: 99%
“…Next cells were lysed and processed according to Gaitonde et al (2000). The antibodies used included: goat anti-PC4 polycolonal antibody (N-17) (Santa Cruz, Santa Cruz, CA, USA) and conformation specific antip53 antibodies: PAb 421, PAb 242, PAb 246 and PAb 240.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
“…After quantitation using scintillation counter an equal amount of protein from each sample was subjected to immunoprecipitation by protein A-sepharose beads conjugated with the conformation specific anti-p53 antibodies: PAb 421, PAb 242, PAb 246 or PAb 240 (Courtesy of Dr David Lane). The beads were processed as described by Gaitonde et al (2000). Samples were electrophoresed on a 10% denaturing polyacrylamide gel.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation